Uncovering the effect of surface basicity on the carbon deposition of Ni/CeO2 catalyst modified by oxides in DRM. (1st March 2023) - Ou, Zhiliang; Ran, Jingyu; Qiu, Huayu; Huang, Xin; Qin, Changlei
Highlights: Effects of basic oxides on catalytic performance of Ni/CeO2 were studies for DRM. Roles of basic site in catalysts on the CO2 adsorption and activation were revealed. Increasing surface basicity improve the resistance to carbon deposition of Ni catalysts. Abstract: The acidity and basicity of Ni based catalysts play very important role in the catalytic performance during dry reforming of methane. Hence, the effects of surface basicity regulated by adding the oxides (CaO, MgO, ZnO and La2 O3 ) in Ni/CeO2 catalysts on the catalytic behavior were systematically investigated, and the characterization methods and DFT calculations were performed to reveal the underlying mechanism. It was found that the addition of basic oxides could improve the activity and stability due to these oxides could increase the adsorbed oxygen, reduce the size of Ni particle and improve the interaction between Ni and support, in particular, the MgO interacts with Ni to form MgNiO2 spinel, which contribute to promote Ni dispersion and inhibit Ni aggregation. Moreover, the results suggested that the resistance to carbon deposition has something to do with the surface basicity. To a certain degree, the increasing the amount of basic site and enhancing alkaline strength could suppress the carbon deposition of Ni based catalysts. This is mainly because that the basic site is beneficial to CO2 adsorption and activation based the DFT calculations, which could accelerate the elimination of carbon deposition by provide more oxygen species. These results could provide some useful information to the design and synthesis of Ni-based catalysts.